Differential Reinforcement Alternative Techniques to Reducing Self-Injury Behaviour in Children with Intellectual Disabilities in SLB Paulus Tomohon - Gusty Prayogo Aziz; Herlina Herlina; Imas Diana Aprilia (INCLUSIVE EDUCATION, 2023)
The research was conducted on Children with Intellectual disabilities in Paulus Tomohon with self-injury. This research has a purpose to get an overview of the effect the DRA technique to reduce self-injury. The research method used was experimental type SSR design A-B. The subject of this research is a student’s grade 1 junior level. The object in this research is behavior self-injury in frequency. The results showed a positive influence towards children, namely a decrease in self-injury behavior by using the DRA technique in terms of occurrence frequency. Evidence of the success of this study is the percentage overlap is 0%. Another evidence is the trend stability of 62.5%(variable) to 83.3%(stable) and at the mean level at A1 5.25 and B 1.08. concluded: by applying the technique of DRA can reduce self-injury in Children with Intellectual disabilities, by transferring word surprises that the subject really likes.